PSYCHOLOGICAL CONSEQUENCES OF BULLYING FOR THE PERSONALITY OF A TEENAGER AND HIS SOCIALIZATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents the views on the psychological consequences of bullying for the personality of a teenager and his socialization, the results of scientific research, the results of analysis in schools, and the cases of harm to each other in adolescents.